Integration of Hydrological and economical aspects for water management in tropical regions. case study: middle Magdalena Valley, Colombia (2020)
Water resources are a determining factor in the economic and social development of communities, given the need that is generated around its use. Over the years, this use has generated pressure on water availability, which were solved by increasing supply, exploring and developing new water sources, and expanding the existing extractions. In Colombia, water concession is the right to the limited use of water, and it is granted to develop economic activity. This concession must be related to water availability to ensure the preservation and efficient water use. However, to allocation water resources efficiently, tools that help to make decisions by analyzing the hydrological regime (surface and groundwater) in areas with lacking reliable data on water availability in an economic context are required. In this context, the main goal of this research was to provide a methodological approximation that allows integrating hydrological, hydrogeological, and economic aspects in water allocation between different users, prioritizing human needs and ecosystem processes, to establish management strategies at a regional scale. In this research performed an integration of diverse hydrological, hydrogeological, and economical aspects, using the Middle Magdalena Valley (MMV) geological basin as a real scale laboratory. Because this area is a primary supply center for the Colombian population, and economic activities related to mining, agriculture, aquaculture, livestock, industrial, services, and O&G exploration and exploitation are developed in conjunction; hydric and economic behavior of the system was analyzed. This analysis was carried out in regards to water availability (surface and groundwater), and its allocation to different stakeholders. For it, three phases were defined: (1.) to characterize the hydrological system, (2.) to characterize the hydrogeological system, and (3.) its integration into an economic optimization model. In the first phase, the hydrologic system behavior was analyzed through a numeric tool, to characterize the water supply, the recharge zones were identified, and the hydrologic alterations affecting the water supply were evaluated. The hydrological modeling allowed to perform an exhaustive interaction analysis between the hydrologic cycle dynamic and the weather condition and land use. Then, it was made an analysis of uncertainty and sensitivity to evaluate the influence of the principal parameters associated with the model. From this analysis, it was validated a methodology allowing to: (i) select proper values for the model parameters, and (ii) evaluate how the model parameters variations influence a simulated response. In the second phase, the geological, hydrological and hydraulic characterization was integrated into a hydrogeological model to estimate the water volume and groundwater flow system description. The result of this phase allowed to consolidate a methodology to assertively restrict a highly parameterized inverse model with lack of information, estimate hydraulic parameters of aquifers and analyze the spatial and temporal variation presented by these parameters at the regional scale. Finally, in the third phase, the hydrological aspects (surface and groundwater) were integrated with an economic optimization framework. This allows them to determine water allocation and water resources quality management. The main objective of this phase was to analyze the water use profit in a regional flow model, integrating multiple water supplies (surface and groundwater) and multiple demands. Here, the allocation model was analyzed from a regional scale in order to consolidate typologies of use by economic sector, and determine management strategies at a regional level. The general results of this research allowed to identify problems and evaluate management strategies, in a tropical basin at the regional level. Additionally, it was concluded that the quantification of water supply affects the allocation process between different stakeholders and this process, in turn, is a function of water quality. As part of the final stage of this research, the water system behavior was analyzed through future scenarios.